Effect of Cu substitution on magnetic behaviour and electrical properties of bilayered manganite La1.2Sr1.5Ca0.3Mn2O7. Issue 1 (17th February 2015) - Saxena, A; Krishnamurthy, A; Srivastava, B K
Abstract: DC magnetization and electrical resistance measurements have been made on 0.5 atomic% Cu substituted bi-layered system La1.2 Sr1.5 Ca0.3 Mn1.99 Cu0.01 O7 for studying the effect of low level substitution of Cu at Mn site. Rietveld analysis of X-Ray diffraction pattern of the sample confirms the single phase Sr3 Ti2 O7 type structure. On cooling below room temperature the system shows magnetic orderings – ferromagnetic (FM) ordering in ab plane below 270K and 3D FM ordering below 45K. Also at an intermediate temperature of 2i0K there is a signature of another transition which could be attributed to onset of an antiferromagnetic state. Substitution of Cu weakens ferromagnetism and the system shows 96% magnetoresistance (MR) at the field of 8 Tesla. The system remains electrical insulator down to 8K. Resistance versus temperature curves has been fitted following Variable range hopping and semiconducting models. Estimated values of density of states at Fermi energy and of Debye temperature are in reasonably good agreement with those reported for other perovskites. Magnetoresistance versus field curves show hysteresis and discontinuities.